ERK/p38 MAP-kinases and PI3K are involved in the differential regulation of B7-H1 expression in DC subsets - Karakhanova, Svetlana; Meisel, Stefan; Ring, Sabine; Mahnke, Karsten; Enk, Alexander (European journal of immunology, 2010)
Regulatory molecules of the B7-H-family expressed by DC are important for immune homeostasis, but their regulation is largely unknown. When investigating the pathways regulating B7-H1 expression in monocyte-derived DC (MoDC), freshly isolated myeloid DC (mDC) and plasmacytoid DC, respectively, we showed that in MoDC and mDC B7-H1 expression was upregulated by a standard cytokine cocktail, poly I:C or LPS. MoDC utilize ERK and PI3K pathways to upregulate B7-H1 in response to cytokines, whereas p38 kinase was predominantly utilized in response to poly I:C. In mDC, ERK and p38 pathways are involved in B7-H1 regulation, and similar to MoDC, mainly p38 signaling was required for poly I:C-induced expression of B7-H1. Plasmacytoid DC responded only to CpG with upregulation of B7-H1 and in addition to p38 also utilized the PI3K and ERK pathways to regulate B7-H1 expression. As a functional consequence of B7-H1 expression on DC, we demonstrate downmodulation of IFN-γ production in T cells. Thus, the differential regulation of B7-H1 on DC subsets may suppress immune responses variably, depending on the target DC population. Further analysis of the regulatory mechanisms may facilitate the development of new immunosuppressive therapies, utilizing the regulation of B7-H1 expression on DC.